Penerapan Model Pembelajaran SAVI Terhadap Hasil Belajar Siswa Pada Mata Pelajaran PPKn Kelas III - Tuken, Ritha; Muslimin; Wanda, Tri (STKIP Andi Matappa Pangkep, 2024)
The problem in this research is the low student learning outcomes in Civics subjects. The objectives of this research are: 1) To determine the process of implementing the SAVI learning model in class III PPKn learning at UPTD SD Negeri 43 Parepare. 2) To determine the improvement in PPKn learning outcomes through the SAVI learning model for class III UPTD students at SD Negeri 43 Parepare. This research approach is a qualitative approach with the type of research being classroom action research. Data collection techniques and procedures are observation, documentation tests and reflection sheets. Next, the data is analyzed and processed descriptively qualitatively. The indicator of the success of this research is if the SAVI implementation process and student learning outcomes are in good qualifications. The results of research in cycle 1 were in sufficient qualifications (C), while the results of research in cycle II were in good qualifications (B). Conclusion: The application of the SAVI learning model can improve learning outcomes in PPKn subjects for class III UPTD students at SD Negeri 43 Parepare.